Huber, Ludwig. Corruption as a social phenomenon. "Romper la mano". A cultural interpretation of corruption. Lima: Proética, Instituto de Estudios Peruanos, 2008, 179 pp. - Mujica, Jaris (2008)
The review does not present a summary